Divergent epidemiology and antimicrobial resistance of bloodstream pathogens: a comparative study in a general tertiary care and a specialized cardiac institute - Khan, Maria; Gul, Amina; Haider, Farooq; Haq, Farman Ul; Khattak, Aakash Ahmad (International Journal of Pathology, 2025)
Background: Bloodstream infections (BSIs) are a critical cause of mortality globally, yet the profile of causative pathogens and their antimicrobial resistance (AMR) patterns vary dramatically across different healthcare settings. This study critically compared the BSI landscape between a specialized cardiac center (Peshawar Institute of Cardiology, PIC), which deals with high-risk nosocomial infections, and a general tertiary care hospital (Khyber Teaching Hospital, KTH), which handles a broad spectrum of community-acquired illnesses.Methods: In total, 7,330 blood culture specimens (6,765 from KTH and 565 from PIC) were processed and rigorously identified. Antimicrobial Susceptibility Testing (AST) was performed using the VITEK 2 Compact Automated System and Kirby-Bauer disc diffusion, interpreted according to CLSI guidelines.Results: The study revealed a bipartite epidemiology of BSIs. At Cardiac Center, the positivity rate was significantly higher (26.9%) and was overwhelmingly dominated by Gram-positive cocci (75%), characteristic of healthcare-associated infections. The principal pathogen was Staphylococcus aureus (48.7%). At General Hospital, the profile was a near-monomicrobial outbreak, with Gram-negative rods predominating (99%). The primary pathogen was Salmonella species (95.7%), reflecting a severe regional burden of community-acquired extensively drug-resistant enteric fever. All tested Gram-positive isolates retained 100% susceptibility to Linezolid, Vancomycin, and Teicoplanin. Similarly, Salmonella isolates showed 100% susceptibility to Carbapenems and Azithromycin. Salmonella exhibited near-universal resistance to Ciprofloxacin (0–2.2% susceptibility) and very poor susceptibility to Ceftriaxone.Conclusion: This study provides a definitive, comparative profile of BSI pathogens in KP, demonstrating that the microbial threat is fundamentally linked to the healthcare environment. The reliance on last-line antibiotics is critical yet threatened by high resistance rates among common oral agents. Immediate clinical and policy action, informed by these institution-specific antibiograms, is urgently required to strengthen Antimicrobial Stewardship Programs and contain the spread of high-priority Multidrug-Resistant organisms.